COMPARISON OF COLIFORM AND NON-COLIFORM BACTERIA CONCENTRATION IN FECES FROM VARIOUS LIFE STAGES OF LAYING HENS - Dharmajaya, Made Tubagus; Suarjana, I Gusti Ketut; Besung, I Nengah Kerta (Buletin Veteriner Udayana, 2020)
This study was conducted to compare the number of coliform and non-coliform bacteria in laying feces on various age groups. This study used a Randomized Block Design (RBD) with four age treatments, namely the starter, grower, developer, and layer phases, respectively. Each treatment used six replications, with a total of 24 samples. The samples obtained were diluted with 10-5 dilutions and planted on Eosin Methylene Blue Agar (EMBA) media. After incubating for 18-24 hours at 37 ° C, the bacteria count was then calculated. Data on the number of coliform and non-coliform bacterial colonies grown on EMBA media were analyzed for variety and continued with BNT test when it was significantly different. The results showed that the number of coliform and non-coliform bacteria in laying hens in various age groups was not significantly different.